Unmet need for contraception and associated factors among women with cardiovascular disease having follow-up at Saint Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia: a cross-sectional study - Negalign Mechal; Mustefa Negash; Hailemichael Bizuneh; Ferid A. Abubeker (BMC, 2022)
Abstract Background Unmet need for contraception refers to the proportion of women who want to postpone or stop childbearing but are not using a contraceptive method. Addressing unmet need is especially important for women with medical conditions such as cardiovascular disease (CVD). Preventing unintended pregnancy is crucial to improve pregnancy outcomes and minimize complications of CVD during pregnancy. However, unmet need for contraceptives continues to undermine the potential benefits of contraceptive use. This research aimed to determine the rate of unmet need for contraceptives and associated factors among women with cardiovascular disease having follow-up at Saint Paul's Hospital Millennium Medical College (SPHMMC), Addis Ababa, Ethiopia. Methods A facility-based cross-sectional study was conducted from February 1 to May 31/2020. A total of 284 reproductive age women with cardiovascular disease having follow-up at the cardiac clinic of SPHMMC were enrolled consecutively until the desired sample size was reached. Data was collected through an exit interview using a structured and pretested questionnaire. Descriptive, bivariate, and multivariable methods were used to analyze the level of unmet need and its associated factors. Results The overall unmet need for contraception was 36.0% (95% CI: 30.4-41.5). The majority of the respondents lack counseling on contraception use. The most common reasons for non-use of a contraceptive method were fear of drug side effects and drug interaction. Unmet need for contraception was found to be more likely among those who have not been counseled on contraceptive utilization (AOR 6.7, CI 1.8-24.7) and those who lack partner support on contraception use (AOR = 6.2, CI: 1.91-19.8). Unmet need was also found to be more likely among women who have never used contraception before (AOR = 3.2, CI 1.12-8.92). Conclusion Unmet need for contraception was high in this high-risk population group. The cardiac follow-up clinic should implement client-centered counseling by a multidisciplinary team to address the needs of women and prevent consequences of unintended pregnancy. Furthermore, there is a need to initiate interventions that encourage communication between couples and increase male partner involvement through a renewed focus on couples counseling.